2015
DOI: 10.17531/ein.2015.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of compressed plates with a cut-out operating in the geometrically nonlinear range

Abstract: Article citation info: (*) Tekst artykułu w polskiej wersji językowej dostępny w elektronicznym wydaniu kwartalnika na stronie www.ein.org.pl IntroductionThin-walled load-carrying structures are characterized by high strength and rigidity as well as low weight. Given the above properties, these structures are widely applied not only in the aerospace and automotive sectors, but also in designs where low structure weight is crucial. A disadvantage of thin-walled structures is that they are prone to loss of stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…They offer a solution to the problem of non-linear stability of the investigated thin-walled structures using experimental and numerical methods [15][16][17][18][19][20]. The investigations of critical and post-critical states as well as the damage of thin-walled composite columns are reported, for instance, in the works [6,7,14,15,[21][22][23][24][25][26][27][28], where the authors present different methods for describing the problem of nonlinear stability Fig. 1 Post-critical equilibrium paths of a plate without initial deflections and of a real structure and validate the developed numerical models in the experimental tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They offer a solution to the problem of non-linear stability of the investigated thin-walled structures using experimental and numerical methods [15][16][17][18][19][20]. The investigations of critical and post-critical states as well as the damage of thin-walled composite columns are reported, for instance, in the works [6,7,14,15,[21][22][23][24][25][26][27][28], where the authors present different methods for describing the problem of nonlinear stability Fig. 1 Post-critical equilibrium paths of a plate without initial deflections and of a real structure and validate the developed numerical models in the experimental tests.…”
Section: Introductionmentioning
confidence: 99%
“…To this end it is necessary to use approximation methods which -based on the post-critical equilibrium paths of a real structure determined in the experiments -enable determination of the critical load. This problem was examined regarding structures made of isotropic materials, for instance, in the work [10,24], and with respect to composite structures in the works [5,7,27,28]. They do not offer, however, a complex procedure which would enable developing an unequivocal methodology for determining the experimental critical load.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, definition of limit load structure elements requires analysis also able post-critical until the destruction of the structure. In the worldwide literature, studies into nonlinear problems of stability of thin-walled structures can be found easily, for example Koiter [13], Debski [5,7], Kopecki [15,17], Mania [21] and [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main problem with steel and composite structures is stability loss, an issue widely described in numerous research publications [1,2,5,6,8,15]. Despite the occurrence of buckling, compressive loads can still be carried by the tested structures, even after exceeding the post-critical condition.…”
Section: Introductionmentioning
confidence: 99%
“…The problems of stability loss and post-critical behavior of thin-walled elements with holes have been described in the publications [6,19]. Axial compression is a common problem in everyday operation of building structures with vast usable areas.…”
Section: Introductionmentioning
confidence: 99%